Subsidies, information, and the timing of children's health care in Mali - Anja Sautmann; Samuel Brown; Mark Dean (Brown University, Department of Economics, 2016)
We study the impact of subsidies (which remove cost barriers) and healthworker visits (which remove informational barriers) on over- and underuse of primary care, using a randomized control trial across 1532 children in Mali. Providing children with access to primary healthcare is an important development goal. Yet the subsidies needed to achieve this may lead to inefficient overuse, particularly if parents have difficulty assessing their child's need for care. For the treatment of acute illness, price elasticities cannot be used to determine welfare effects, because they do not provide information on whether care is used effectively, which in turn depends on when it is sought. We propose a dynamic model of healthcare timing and define over- and underuse as seeking care too early or too late during an illness spell. We then use nine weeks of daily health records to identify misuse in our sample relative to WHO standards of care. Hazard estimates of care seeking show substantial underuse, but almost no overuse in our population. The primary barrier to the optimal timing of care seeking is cost, not information: subsidies increase care seeking by about 250%, and only 18% of this increase constitutes overuse. In contrast, healthworkers do little to reduce (already minimal) overuse, and may increase underuse when not paired with free care, as we predict in our dynamic model. Free care increases the value of care consumed without crowding out private spending, and it reduces mothers' concern and average illness duration.
Keywords: 330